Penyusunan Rencana Strategis Bisnis RSUD Kebayoran Baru: Rencana Strategi Pemasaran - Rabiulyati, May; Nurwahyuni, Atik; Sulistiadi, Wachyu (Syntax Literate, 2023)
The Draft Strategic Business Plan for RSUD Kebayoran Baru was formed, where currently RSUD Kebayoran Baru is in cell V Hold and Maintain, with the recommended strategies being market penetration and product development. It is necessary to develop a marketing strategy in order to increase visits from neurological poly patients, in particular, increasing market share through collaboration with private insurance, travel agents, hotels or other companies in the area. Another strategy is to conduct seminars and monitor patient engagement with views, likes, comments, shares and satisfaction figures on Google reviews. Recommendations for improving service quality, increasing advertising/marketing outside the building, and strong commitment from all leaders and staff for the successful implementation of the hospital's strategic plan.